Prevention and resolution of land conflicts in the community in Suka Makmur Village - Wantu, Fence M.; Daud, Akbar Hudayatullah; Sarson, Mohamad Taufiq Zulfikar; Sarjono, Anastasia; Umar, Nurifana; Elmarianti; Aulia, Nur Insani (Society : Jurnal Pengabdian Masyarakat, 2026)
Land is a fundamental element with economic and social dimensions that are often a source of conflict due to the imbalance between the rule of positive Law (law in books) and practice in society (law in action). In Suka Makmur Village, low legal literacy and a strong tradition of underhand transactions create legal vulnerabilities and make land a "dead capital" (dead capital). This activity aims to increase public understanding of the importance of land certification through the complete systematic land registration (PTSL) program and provide basic skills in non-litigation dispute resolution. The implementation uses a participatory approach that combines normative and sociological aspects through three stages: (1) observation and identification of conflict typology; (2) socialization and legal education; and (3) Discussion and clinical consultation in the form of surgical cases of citizens ' land documents. It was found that the dominant conflicts in the village were boundary disputes and inheritance disputes. This activity succeeded in changing the public's perception of land certification, which was originally considered expensive, into an economical preventive measure. Prevention is carried out through strengthening the understanding of the principle of Contradictoire Delimitatie (mutual delimitation), while dispute resolution is directed at village mediation mechanisms that are seen as more humanistic and effective in maintaining social cohesion than litigation channels. The synergy between citizens ' legal awareness, Village Administrative Order, and the use of government programs (PTSL) is the main key in mitigating and resolving land disputes in a sustainable manner.